Plasmonic Demultiplexer With Tunable Output Power Ratio Based on Metal-Dielectric-Metal Structure and E7 Liquid Crystal Arrays - Zelong Wang; Lin Cheng; Yuyao Wu; Chengpu Li; Mingyang Gong; Pengfei Cao; Xiaodong He; Tiaoming Niu (IEEE Photonics Journal)
A novel tunable plasmonic demultiplexer is proposed and numerically investigated by finite element method (FEM). It consists of two half-nanodisk cavities and two sets of E7 liquid crystal arrays which are side-coupled to three metal-dielectric-metal (MDM) waveguides. The demultiplexer can split the input lights into two parts corresponding to port1 (1310 nm) and port2 (1550 nm). The Q-factors of port1 and port2 are 54.6 and 36, and the crosstalk values are −20.7 dB and −29.9 dB, respectively. Obviously, both channels have high Q-factors and low crosstalk value. Moreover, the E7 liquid crystal arrays play a key role in the whole structure, which makes the output power adjustable proportionally by adjusting the applied voltage. This novel feature greatly enriches the function of our demultiplexer. Using the electronical tunable birefringence characteristic of liquid crystal and its arrays structure paves a new way to realize practical on-chip plasmonic system, which can be widely used not only in demultiplexers but also in nanosensors, optical splitters, filters, optical switches, nonlinear photonic and slow-light devices.